INTERNET-BASED DISCLOSURE AND FIRM VALUATION - Natama, Jennifer Magdalena; Nainggolan, Yunieta Anny (Journal of Business and Management, 2018)
Abstract : Goal of a company is to maximize its shareholder’s wealth which can be seen from its firm value. There are several factors affecting firm’s value, including disclosure. In theory, the more information a shareholder know about a company, the easier it is for them to value a company. Unfortunately, there are occurance of information assymetry that firm valuation ineffective. One of the way to mitigate information assymetry is through internal and external policies applied. External policies means government or local authorities called mandatory disclosure. However, Indonesia’s regulation is not strong enough. This phenomenon need internal policies to mitigate the problem through corporate governance policies. Disclosure that regulates inside company called voluntary disclosure. Both disclosure can take form in financial or non financial information. To make sure that information received properly, it has to come in an effective media. Internet is suspected to be the most effective media to disclose information. The author finds that there are strong relationship between companies’ disclosure level and firm value. Disclosure have positive correlation with ROA and negative correlation with Tobin’s Q. It shows that by disclose more information to public, company will have a greater profitability but, will generate lower market value. From this findings, it can conclude that although disclosure can increase profitability, but it is not working in reduce information asymmetry and therefor did not generate a greater market value.Keywords:  Internet of Things, Company Disclosure, Firm Value, Company Website.